An in silico study of the citrus dioxygenases CCD4 family substrates. Issue 8 (24th May 2019) - Vega-Teijido, Mauricio; Cantero, Jorge; Rodrigo, Maria J.; López, Carolina; Zunini, Margot Paulino
Abstract: The coloration of Citrus fruits is related with the concentration of carotenoids, isoprenoid pigments of 40 carbon atoms (C40 ). Rodrigo et al. and Ma et al. reported a CCD4-type citrus dioxygenase responsible for the generation of C30 apocarotenoids providing a reddish-orange pigmentation to the peel of many mandarins and oranges. Among them, CCD4b was the first case described of a dioxygenase that cleaves carotenoids C40 in the double bond 7′, 8′ or 7, 8, generating β-citraurin or 8-β-apocarotenal. Here we report the three-dimensional structures of CCD4a and CCD4b, modeled by sequence homology (2BIW) and validated by molecular dynamics (MD). Docking calculations were performed in CCD4a and CCD4b structures with thousands of rotated initial carotenoid conformations and all the possible poses in the active site were found. The interaction energy was measured by means of ASE scoring, Amber99 refinement and London Δ G rescoring. For the case of CCD4a model, the results showed London Δ G score of −19, −17 and −15 kcal/mol for zeaxanthin, β-cryptoxanthin and β-carotene, respectively. The same sequence in the estimated interaction strength for the three ligands was obtained using MD. The interaction energy of CCD4b indicated that, in agreement with experimental data, zeaxanthin and β-cryptoxanthin could be cleaved by the enzyme, β- and α-carotene have chances to be oxidized and lycopene has not good interaction energy to be predicted as substrate. These findings will be discussed considering the potential in vivo substrates and products, and the physiological role in Citrus fruits. Communicated by Ramaswamy H. Sarma